2011
DOI: 10.1002/aic.12740
|View full text |Cite
|
Sign up to set email alerts
|

Design of a model‐based feedback controller for active sorting and synchronization of droplets in a microfluidic loop

Abstract: in Wiley Online Library (wileyonlinelibrary.com).The transport of confined droplets in fluidic networks can lead to complex spatiotemporal dynamics, precluding full control of the position of droplets in the network. Here, we report the design of a model-based feedback controller that can actively regulate droplet positions in a network. We specifically consider droplet dynamics in a microfluidic loop where a main channel splits into two and recombines. Consistent with previous studies, we find that without ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Confined droplet dynamics is predicted using the network model under the assumption that the droplets do not collide [14]. The network model has been shown to satisfactorily predict the droplet dynamics in microfluidic loop [15] and ladder networks [16,17]. In this model, drops are treated as point objects moving at a velocity v = βQ/S [18][19][20], where β is the slip factor, S is the cross-sectional area, and Q is the flow rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Confined droplet dynamics is predicted using the network model under the assumption that the droplets do not collide [14]. The network model has been shown to satisfactorily predict the droplet dynamics in microfluidic loop [15] and ladder networks [16,17]. In this model, drops are treated as point objects moving at a velocity v = βQ/S [18][19][20], where β is the slip factor, S is the cross-sectional area, and Q is the flow rate.…”
mentioning
confidence: 99%
“…This slight asymmetry ensures that the droplet decisions are deterministic. The resistance of the branch is summation of the resistance of the channel [15] and resistance due to drops (nR d ), where n is the number of drops in the branch and R d is the excess hydrodynamical resistance per drop. Using this network model, we illustrate the QDS principle with two representative scenarios: 3-period and 9-period behaviors, without input fluctuations.…”
mentioning
confidence: 99%
“…The network model has been validated in a number of studies. In our prior work (Maddala et al, 2011), we have shown that the model can predict complex behavior that are experimentally observed in simple loop devices. Further, we have shown that the network model can also be used in ladder devices (Maddala & Rengaswamy, 2014).…”
Section: Main Simulation Equationsmentioning
confidence: 99%
“…In this work, the continuous variables are taken from literature (Maddala et al, 2011;Maddala & Rengaswamy, 2014) and the discrete variables are optimized using genetic algorithm.…”
Section: Model Description and Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation